Žledolom januarja in februarja 2014 v Sloveniji - Sinjur, Iztok (Gozdarski vestnik, 2014)
The ice storm that hit Slovenia in the period between 31 January and 5 February 2014 caused a huge damage in forests. Weather phenomena were not exceptional only by the duration and the extent but consequently also by amount of damage. A lot of Slovenian forests were seriously damaged. The article describes causes for this ice storm and explains reasons for spatial variability of damage in the forests. Analysis is based on various meteorological stations% data and other systems for meteorological observations and was done with the support of Life+ ManFor C.BD project.
Keywords: žled; temperatura zraka; gozdovi; dinarski svet; Slovenia; Slovenija; 2014